Decreasing Emergency Department Boarding Times for the Intensive Care Patient - Berry, Peter (My University, 2021)
When critically ill patients arrive in the ED, substantial resources are reallocated to the patient, moving the supplies and hospital personnel away from others. Critically ill patients are remaining in the ED waiting on admission to the ICU, some higher than six hours. The delay in admission to the ICU puts the critically ill patient at risk for harmful outcomes in an environment where the resources are already stretched. This project aimed to decrease the ED boarding time for the patient who requires admission to the ICU. This process ensures high-quality care for critically ill patients in the ED and a fast transfer from the ED to the ICU with a continuous open bed availability in the ICU for critically ill patients arriving in the ED. This process would assist to ensure effective patient throughput and decrease the ED LOS for the patient requiring the ICU higher level of care. In an effort to reduce the time critically ill patients are boarding in the ED, a simple protocol of staying a “bed ahead” in the ICU would be followed during the project period. The ICU would keep a minimum of one bed available for admissions from the ED to immediately accept a patient accepted by the Critical Care Medicine team. With this project, there was a decrease in the transfer times from an average of 6.5 hours to 5.0 hours overall, for a 1.6-hour reduction in boarding time. This process allows for the ICU level of care to start sooner, and the orders from the critical care team are carried out and completed more expeditiously.
Keywords: intensive care unit; emergency department; length of stay; patient flow; patient throughput; emergency department boarding